The Nightmare charade - Arnett, Mindee (Tor Teen, 2015)
At Arkwell Academy, a boarding school for "magickind," sixteen-year-old Dusty Everhart, a magical being who feeds on human dreams, and her dream partner Eli Booker fall in love and are sent on a dangerous mission to obtain the Death's Heart.